Пошаговое объяснение:
1 . М(16;7;-8), К(8;-9; -6) ; A(x₀ ; y₀ ; z₀ ) - ?
x₀ = ( 16 + 8 )/2 = 12 ; y₀ = ( 7 - 9 )/2 = - 1 ; z₀ = ( - 8 - 6 )/2 = - 7 ; A(12 ;- 1 ; -7 ) .
2 . К(3; -1; 2), С(1;3;-5) ; B( x₂ ; y₂ ; z₂ ) - ?
( 3 + x₂ )/2 = 1 ; 3 + x₂= 2 ; x₂ = - 1 ;
( - 1 + y₂ )/2 = 3 ; - 1 + y₂ = 6 ; y₂ = 7 ;
( 2 + z₂ )/2 = - 5 ; 2 + z₂ = - 10 ; z₂ = - 12 ; B( - 1 ; 7 ; - 12 ) .
3 . А(5;-1; 4), В(9;1;8) ; AB -?
AB = √[ ( 9 - 5 )²+ ( 1 + 1 )²+ ( 8 - 4 )²] = √ ( 16 + 4 + 16 ) =√ 36 = 6 ; AB = 6 .
4 . А(-2;1;4), С(2;3;-2), D (1;0;-1) ; B( x₂ ; y₂ ; z₂ ) - ?
Вектор AB = DC ; знайдемо координати цих векторів :
AB( x₂ + 2 ; y₂ - 1 ; z₂ - 4 ) = DC( 1 ; 3 ;- 1 ) ; звідси
x₂ + 2 =1 ; х₂ = 1 - 2 ; х₂ = - 1 ;
y₂ - 1 = 3 ; у₂ = 3 + 1 ; у₂ = 4 ;
z₂ - 4 = - 1 ; z₂ = 4 - 1 ; z₂ = 3 ; отже , В( - 1 ; 4 ; 3 ) .
n = 10
Пошаговое объяснение:
(n! + (n+2)!) / (n+1)! = 133/11
Заметим, что:
(n+1)! = n!*(n+1)
(n+2)! = n!*(n+1)(n+2)
Подставляем в уравнение.
(n! + n!*(n+1)(n+2)) / (n!*(n+1)) = 133/11
Сокращаем n!
(1 + (n+1)(n+2)) / (n+1) = 133/11
(1 + n^2 + 3n + 2) / (n+1) = 133/11
По правилу пропорции
11(n^2 + 3n + 3) = 133(n+1)
11n^2 + 33n + 33 = 133n + 133
11n^2 - 100n - 100 = 0
D = 100^2 - 4*11(-100) = 10000 + 4400 = 14400 = 120^2
n1 = (100 - 120)/22 = -20/22 < 0 - не подходит
n2 = (100 + 120)/22 = 220/22 = 10 - подходит.